QUESTIONING CANONICAL ART HISTORY: RECORDING MÜRECCEL KÜÇÜKAKSOY AND MUKADDES SARAN IN HISTORY - Okkali, Ilkay Canan; Dastarli, Elif (E.U. Printing and Publishing House, 2024)
This article examines the lives and art of two women artists, Mukaddes Saran and M & uuml;reccel K & uuml;& ccedil;& uuml;kaksoy, as subjects, while deciphering the canon of Turkish modern art history. Saran and K & uuml;& ccedil;& uuml;kaksoy preferred mostly figurative work, distancing from the debates of figurative-non-figurative painting opposition of the 1950s in Turkey. The friendship that began at the Istanbul State Academy of Fine Arts between the two artists continued until the end of their lives with a feminist solidarity akin to sisterhood, and they probably influenced each other both in terms of subject matter and technique. Both K & uuml;& ccedil;& uuml;kaksoy and Saran primarily worked about portrait and landscape in a naturalistic style, with Saran's expressive style becoming more prominent in later years. However, both artists' chosen subjects and overall styles are outside the canon of modern Turkish art. Since the late 1920s,- male- artist-writers, and since the 1940s, art historians, have written Turkish modern art history, setting the paradox of modernization as the main axis and hierarchically placing both the modernist style and the modernist male artist at the top. The article emphasizes how this art history has created epistemic injustice against women. On the other hand, this study draws attention to the reasons that led many academically educated women artists in Turkey, especially K & uuml;& ccedil;& uuml;kaksoy and Saran, to focus on subjects such as portrait and still life and work in a naturalistic style until the rise of contemporary art. Certainly, this situation is a natural consequence of reasons such as the responsibility of women artists for home and family care, the lack of professional time to devote to art in their daily lives, the absence of their own studios, the inability to access live models, and the lack of active engagement with the global art scene, which are available to men but are lacking for women. The efforts of K & uuml;& ccedil;& uuml;kaksoy and Saran to exist within these unequal artistic conditions are attempted to be understood and recorded in the article, thus drawing attention to the conditions that position women artists not as professionals in the art scene but rather as artists interested in art as a hobby. In a biographically based art history writing, it is essential to question whether the personalities, families, friendships, experiences, traumas, etc., of the artists, and even their characters, relate to their works and contribute to art history writing. Therefore, the article not only limits itself to recording the life stories of K & uuml;& ccedil;& uuml;kaksoy and Saran and examining their works but also attempts to determine their positions within the teacher-student relationships, classmate friendships, studio partnerships, and collaborations in joint exhibitions during the periods they worked. It is evident that women artists have strived to exist and create under challenging conditions in every period of art history. However, the article suggests that art history should go beyond merely emphasizing these hardships in women artists lives, and the article itself claims to be a writing of art history that breaks the canonical narrative.
Keywords: woman artist; M & uuml; reccel (Duygu/Duyguer/& Ouml; zsever) K & uuml; & ccedil; & uuml; kaksoy; Mukaddes (Erol) Saran; Turkish painting art; art history canon; Art